Malaria and malnutrition co-existence among under-five children of tribal dense regions of Odisha: a community based study - Mahapatra, Ashish; Mohapatra, Sabyasachi; Mitter, Niloy; Dash, Sushree Swagata; Mishra, Rudra Prasanna; Satapathy, Durga Madhab (International Journal Of Community Medicine And Public Health, 2018)
Background: “Malaria and malnutrition are closely related in the months of hunger gap when malnutrition is at its peak often coincides with rainy season when the number of malaria cases shoot up. The disease combines in a vicious circle. Children sick with malaria are more likely to become dangerously malnourished”. Severely malnourished children with malaria infection may have no fever, or be hypothermic. Proactive screening for malaria in severely malnourished children is needed even if the child has no symptoms of malaria. The objectives of the study were to estimate prevalence of “malaria and malnutrition” co-existence in under 5 children of tribal dense regions and to determine if any significant difference between this co-existent condition against the disease alone. Methods: Eight villages were selected based on their inaccessibility and demography spread across Bamnipal and Sukinda region. Malaria testing using antigen based RDK and nutritional assessment using MUAC tapes were conducted in of 6 months to <5 yrs children. Results: A total of 224 children of under 5 yrs age group were screened. 50.4% of them were suffering from malaria, 38% of the children were at risk or suffering from severe acute malnutrition. Of the 113 children with malaria, 45% were having malnutrition. Out of 86 malnourished children 59% were diagnosed with malaria. 22.7% of children were found to have malaria and malnutrition together. Conclusions: Malaria and Malnutrition are co-existent and synergistic to each other.